2017
DOI: 10.1111/ejn.13537
|View full text |Cite
|
Sign up to set email alerts
|

Learning new sequential stepping patterns requires striatal plasticity during the earliest phase of acquisition

Abstract: Animals including humans execute motor behavior to reach their goals. For this purpose, they must choose correct strategies according to environmental conditions and shape many parameters of their movements, including their serial order and timing. To investigate the neurobiology underlying such skills, we used a multi-sensor equipped, motor-driven running wheel with adjustable sequences of foothold pegs on which mice ran to obtain water reward. When the peg patterns changed from a familiar pattern to a new pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 53 publications
(61 reference statements)
2
20
0
Order By: Relevance
“…Furthermore, the functional significance of NO-LTD is unclear. A recent study shows that the NO-synthesizing plateau and low threshold spike interneurons (PLTSIs) are recruited (in addition to iSPNs and dSPNs) in learning of new sequential stepping patterns (Nakamura et al 2017), suggesting that NO-LTD may be essential for certain types of striatum-dependent learning.…”
Section: More Than One Form Of Long-term Depression In the Striatum?mentioning
confidence: 99%
“…Furthermore, the functional significance of NO-LTD is unclear. A recent study shows that the NO-synthesizing plateau and low threshold spike interneurons (PLTSIs) are recruited (in addition to iSPNs and dSPNs) in learning of new sequential stepping patterns (Nakamura et al 2017), suggesting that NO-LTD may be essential for certain types of striatum-dependent learning.…”
Section: More Than One Form Of Long-term Depression In the Striatum?mentioning
confidence: 99%
“…This striking finding indicates that there is abnormal plasticity in corticostriatal or thalamostriatal circuits, or other intrinsic basal ganglia circuits impacting striatal function (Mallet et al, 2012) possibly related to the delayed sensorimotor learning that we found in the CDGI mutant mice. NMDA receptor function in the dorsolateral (sensorimotor) striatum, which is particularly enriched for CDGI expression, is essential for normal learning on the wheelrunning assay that we used (Nakamura et al, 2017). Thus, the NMDA signaling abnormalities in the striatum of CDGI mutants might directly underlie their slowed learning in this task.…”
Section: Discussionmentioning
confidence: 99%
“…The CDGI knockout mice showed no deficits in the allocentric maze task, or in assays of amygdaloid complex function ( Figure S3). We next tested the knockout mice on a sensitive peg-wheel running assay of striatal learning (Kitsukawa et al, 2011;Nakamura et al, 2017) in which the arrangement of the wheel's left and right footstep pegs could be changed to test the ability of the mice to learn different running patterns ( Figures 2B and S3). Learning was measured as reduced variance in the timing of paw-placement on the pegs.…”
Section: Cdgi Mutations Are Associated With Abnormal Striatum-based Bmentioning
confidence: 99%
See 2 more Smart Citations